PENURUNAN KADAR LOGAM BESI MENGGUNAKAN BUBUK KALSIUM CANGKANG KERANG HIJAU - Noorma Kurnyawaty; Fitriyana Fitriyana; Muhammad Taufik; Ayu Erika Putri (JURNAL TEKNIK KIMIA VOKASIONAL (JIMSI), 2021)
Green mussels (Perna viridis) are a type of processed water from a fairly high percentage of production. The high consumption rate is followed by the high amount of residual processing waste produced, namely in the form of shells. Unfortunately, mussel shell is a waste that is not used optimally. In the shells, there are a lot of mineral content, which when processed many benefits will be obtained. Clamshells have been studied to contain a fairly high source of the mineral calcium. This study is preliminary research focused on determining the ability of green mussel shell calcium powder to reduce iron levels in standard solutions with concentrations of 20, 40, 60, 80, and 100 mg / L. The results obtained from this study are the calcium content of green clamshells in the form of calcium carbonate (CaCO3) with calcium reaching 34.93% Wt and can be used properly to reduce iron metal levels.